AStudy on Efficacy of Topiramate in Reducing Migraine Related Disability and Pain - AMM, Safna; S, Suchandra (Indian Journal of Pharmacy Practice)
Migraine, a chronic neurological disorder accounts for about 90% of the total workdays lost by an individual. Migraine with a peak onset of action at second and third decades of life exerts a tremendous burden on patients' personal and social functioning and undermines the normal function and productivity. Migraine related disability assessment is crucial to provide a rational basis for treatment. The disruption caused by migraine is assessed by using Migraine Disability Assessment Scale (MIDAS) and Mc-Gill pain scale questionnaires. The patients who were newly diagnosed with migraine with no abnormalities on neurological examination aged 18 – 65 years were included in the study. Patients were asked to fill the questionnaire at baseline (before starting the drug therapy) and at final visit (3 months after drug therapy). There was a significant (p ≤0.01) improvement in the Migraine Disability Assessment Scale (MIDAS) and Mc-Gill pain scales in the final visit from the baseline. This prospective study thus revealed Topiramate is efficacious in reducing migraine related disability, pain and also improve the ability to function in their daily lives. Individual patient care and patient counseling may improve patient compliance in migraine which leads to better therapeutic efficacy.
Keywords: Disability; Midas; Migraine; MC-gill Pain Scale; Topiramate